1995
DOI: 10.1016/s0886-3350(13)80137-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate visual capability after cataract surgery: Topical versus retrobulbar anesthesia

Abstract: This study evaluated vision immediately after surgery in 56 consecutive patients (31 who had topical anesthesia and 25 who had retrobulbar anesthesia) for cataract extraction by phacoemulsification and intraocular lens implantation. An unbiased, trained nurse measured uncorrected and best corrected visual acuities one hour, one day, and one week after surgery. One hour after surgery, patients in the topical anesthesia group had significantly better visual acuity than those in the retrobulbar anesthesia group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 6 publications
1
19
0
2
Order By: Relevance
“…29,30 Martini et al 12 showed that topical ropivacaine is safe in endothelial toxicity and seemed to be a good alternative to lidocaine, but could cause transient corneal oedema. None of our patients in the ropivacaine group displayed any kind of corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Martini et al 12 showed that topical ropivacaine is safe in endothelial toxicity and seemed to be a good alternative to lidocaine, but could cause transient corneal oedema. None of our patients in the ropivacaine group displayed any kind of corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of surveys of members of the American Society of Cataract and Refractive Surgery, Leaming 1 showed that the percentage of respondents who reported topical anaesthesia as their primary method of anaesthesia increased from 0.2% in 1993 to 37% in 1998, 2 and 61% in 2003. 3 Topical anaesthesia has several advantages over regional anaesthesia: unlike injection anaesthetic techniques, there is rapid return of postoperative visual acuity, 4 no postoperative ptosis or diplopia, 4 and no risk of damage to the globe or orbital contents. [5][6][7] It is only in recent years that patients' intraoperative visual experience during cataract surgery using different forms of local (topical, peribulbar, retrobulbar, and sub-Tenon's) anaesthesia has been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Topical anesthesia has additional benefits like not interfering with visual function, immediate visual recovery, absence of pain due to injection, unlimited ocular motility, and absence of an increase in orbital volume and resultant rise of IOP. 11 Various studies regard Mithal C, Agarwal A, Mithal N Cataract surgery under topical anesthesia Nepl J Ophthalmol 2012; 4 (7): 114-118 117 compairing the pain perception and patients' acceptability for anesthetic technique have been done and they concluded that the patients' satisfaction for anesthesia is comparable for topical versus other techniques. 12,13 Fichman (1996) has investigated the blood pressure, pulse rate, and respiration rate of patients during surgery under topical anesthesia and has found no major changes in these parameters.…”
Section: Discussionmentioning
confidence: 99%